(untitled) - Cleveland P. Hickman (Boston, Mas., 1997)
The book is divided into four parts. Part one sets the stage with basic principles, emphasizing evolution as the keystone of biology. Part twwo deals with the form and function of animals. Part three and four cover the range of animal diversity of invertebrates and vertebrates, respectively
Keywords: zoology